2019
DOI: 10.1016/j.heliyon.2019.e02431
|View full text |Cite
|
Sign up to set email alerts
|

Changes in stability and shelf-life of ultra-high temperature treated milk during long term storage at different temperatures

Abstract: In the ultra-high temperature (UHT) process, milk is subject to temperatures above 135 °C for few seconds giving a product with a shelf-life of several months. The raw milk quality, UHT process and storage conditions affect the stability. In this study, the stability of UHT milk produced in an indirect system was evaluated by studying changes in taste, colour, fat separation, fat adhesion to the package, sedimentation, gelation, heat coagulation time, pH and ethanol stability during storage for up to one year … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 27 publications
2
21
0
3
Order By: Relevance
“…On the last day of the DMD, the sweet cream maintained sensory quality. Similarly, this was observed in the research conducted by Karlsson et al [41], whose results confirmed that refrigerated or ambient storage temperatures were conditions that gave good sensory properties for UHT milk. Only small flavour deviations were found after long-term storage at 4 and 20 • C. Nevertheless, significant changes were observed regarding the sensory characteristics of the sweet cream in the samples that had been stored for 6 months.…”
Section: Discussionsupporting
confidence: 85%
“…On the last day of the DMD, the sweet cream maintained sensory quality. Similarly, this was observed in the research conducted by Karlsson et al [41], whose results confirmed that refrigerated or ambient storage temperatures were conditions that gave good sensory properties for UHT milk. Only small flavour deviations were found after long-term storage at 4 and 20 • C. Nevertheless, significant changes were observed regarding the sensory characteristics of the sweet cream in the samples that had been stored for 6 months.…”
Section: Discussionsupporting
confidence: 85%
“…Storage time and storage temperature were not part of the full factorial designed model to evaluate the effects of calcium, citrate, and urea. However, it is know that storage temperature and storage time affect the stability of UHT milk [19]. Our results show that independent of storage temperature, storage time was closely connected to fat separation and fat adhesion, i.e., the longer the storage, the more fat was floating on the surface and adhering to the package (Figure 2).…”
Section: Resultsmentioning
confidence: 65%
“…Fat separation, fat adhesion, sediment formation, and color were measured as described in Karlsson et al [19]. Fat separation was defined as the thickness of the cream layer floating on the surface and rated on a four-graded scale, i.e., no visual cream layer, waves of cream, a surface completely covered with fat or lumps/clots of fat.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Storage temperature may cause a change in the number and mutual proportions of lactic acid bacteria to the typical composition for the yoghurt, thus to its acidification and pH [16]. The recommended storage temperature of yoghurt ranges from 1°C to 8°C, but its stability may be extended by storing at 4°C or less during the whole shelf life [17]. The easiest and most efficient way of prolonging food shelf-life is to use natural or artificial preservatives; however, evidence indicates that most artificial preservatives damage the human body in various degrees [18].…”
Section: Introductionmentioning
confidence: 99%